The role of the athletes' entourage on attitudes to doping - Barkoukis, V.; Brooke, L.; Ntoumanis, Nikos; Smith, B.; Gucciardi, Daniel (TAYLOR & FRANCIS LTD, 2019)
The present study investigated athletes' and coaches' beliefs about the role of athletes' entourage in deterring or promoting doping. Competitive athletes and coaches in Greece and Australia took part in semi-structured interviews. Our analysis of the interviews produced five main themes: coach influence, peer influence, doping stance, doping stigma, and entourage's culture. Overall, coaches and peers having a close and trusty relationship with the athletes were considered most influential with respect to doping-related decisions. The majority of the athletes held a strong anti-doping stance but could not articulate why they held this position. This inability could be ascribed to the stigmatization of doping which led to lack of knowledge and anti-doping education. Finally, an anti-doping culture in the athletes' environment was considered central to an anti-doping stance. The study findings provide valuable information towards a comprehensive understanding of the role athletes' entourage can play in shaping athletes' attitudes and decision for doping.